2014
DOI: 10.1186/1475-2875-13-336
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected detection of Plasmodium vivax and Plasmodium falciparum DNA in asymptomatic blood donors: fact or artifact?

Abstract: A study searching for Plasmodium vivax and Plasmodium falciparum DNA among blood donors from the non-endemic area in Brazil reported a rate of 7.41%. This number is at least three times higher than what has been observed in blood donors from the Amazon, an endemic area concentrating >99% of all malaria cases in Brazil. Moreover, the majority of the donors were supposedly infected by P. falciparum, a rare finding both in men and anophelines from the Atlantic forest. These findings shall be taken with caution si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Recently, a cross-sectional study revealed a surprisingly high frequency (5.14%, 57/1,108) of P. falciparum real-time PCR positivity in asymptomatic blood donors living or in close contact with forested regions of the southeastern Brazilian Atlantic forest biome [ 21 ]. The bromeliad-malaria paradigm would predict no P. falciparum infection and very low frequency of P. vivax infection in asymptomatic blood donors inhabiting forested areas of São Paulo state [ 22 ]. In fact, Mendrone et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a cross-sectional study revealed a surprisingly high frequency (5.14%, 57/1,108) of P. falciparum real-time PCR positivity in asymptomatic blood donors living or in close contact with forested regions of the southeastern Brazilian Atlantic forest biome [ 21 ]. The bromeliad-malaria paradigm would predict no P. falciparum infection and very low frequency of P. vivax infection in asymptomatic blood donors inhabiting forested areas of São Paulo state [ 22 ]. In fact, Mendrone et al .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Mendrone et al . [ 22 ] suggested that the P. falciparum real-time PCR positivity found in asymptomatic blood donors [ 21 ] could be an artifact. However, another study proposed that alternative dynamics of Plasmodium transmission may have evolved and caused the unexpected high frequencies of P. falciparum DNA in humans, the high level of antibodies against CSP in monkeys and Plasmodium -infected mosquito species other than Kerteszia [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies of ITWL using insecticide-treated plastic sheeting (ITPS) demonstrated high mosquito mortality and reductions in malaria incidence in temporary labour shelters and refugee camps [ 17 – 20 ]. Subsequent, experimental hut trials of both pyrethroid and non-pyrethroid ITPS compared with LLINs have presented more equivocal results, which have been attributed to varying levels of insecticide resistance among vector populations [ 21 27 ]. The only community-level trial to evaluate carbamate-treated ITPS in combination with LLINs in an area of pyrethroid resistance in Benin reported no additional protection against malaria, potentially due to limited wall coverage and residual activity of the carbamate applied [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 2001–2004 study [ 4 ], it was used a multiplex PCR described by Rubio et al [ 27 ]. As the use of multiplex PCR may have affected the specificity of the test, the finding of P. falciparum DNA in this region may represent artifacts of the technique, indicating the presence of a species that is not in fact part of the transmission chain [ 28 ]. Nevertheless, in a recent study in fragments of Atlantic Forest in the southeast of Brazil, Laporta et al [ 29 ] identified anophelines naturally infected with P. falciparum and P. vivax , the latter in a smaller proportion of the infected mosquitoes.…”
Section: Discussionmentioning
confidence: 99%